PENGARUH PENGGUNAAN TEPUNG BIJI NANGKA (Artocarpus heterophyllus) DALAM PAKAN TERHADAP BOBOT GIBLET AYAM PEDAGING - Ulfa Tiara Pangesti; M Halim Natsir; Edhy Sudjarwo (TERNAK TROPIKA Journal of Tropical Animal Production, 2016)
The purpose of this study was to determine the effect used of jackfruit seed meal in diet on broiler giblet weights. The materials of this study were 100 birds of New Lohman MB-202 P broiler chicks with average 37,77 unsexing. The method of this experiment was Completly Randomize Design (CRD) with 4 treatment and 5 replication, if there were significant effect, it would tested by Duncan’s Multiple Range Test Method, and continued with Simple Linear Regression. The result showed that the jackfruit seed meal in broiler diet gave significant effect (P>0,01) on final weight, heart weight, liver weight, gizzard weight and spleen weight. The jackfruit seed meal had a negatif correlation with final weight, heart weight, liver weight, gizzard weight and spleen weight. It had conclude that jackfruit seed meal can be used up to the level of  5% in broiler diet, viewed from the final weight, weight of the heart, liver, gizzard, and spleen, because the weights are not significantly different with diet without the use of jackfruit seed meal. Keywords : Broiler, Jackfruit Seed Meal, Giblet